2019
DOI: 10.3390/cells8121483
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lysyl Oxidase Enzymes in Cardiac Function and Remodeling

Abstract: Lysyl oxidase (LOX) proteins comprise a family of five copper-dependent enzymes (LOX and four LOX-like isoenzymes (LOXL1-4)) critical for extracellular matrix (ECM) homeostasis and remodeling. The primary role of LOX enzymes is to oxidize lysyl and hydroxylysyl residues from collagen and elastin chains into highly reactive aldehydes, which spontaneously react with surrounding amino groups and other aldehydes to form inter-and intra-catenary covalent cross-linkages. Therefore, they are essential for the synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 97 publications
2
46
0
Order By: Relevance
“…In females, the remodeling of the sarcomeric cytoskeleton in cardiomyocytes under hemodynamic load might be responsible for greater stiffness and lower LV compliance, thus resulting in more severe impairment of the cardiac function [50] than that in males. Additionally, aberrant collagen cross-linking has been reported to be more detrimental to LV diastolic and systolic performance than total collagen deposition in the ECM [4,51].…”
Section: Correlation Between LV Mir-29b Expression and Morpho-functiomentioning
confidence: 99%
See 1 more Smart Citation
“…In females, the remodeling of the sarcomeric cytoskeleton in cardiomyocytes under hemodynamic load might be responsible for greater stiffness and lower LV compliance, thus resulting in more severe impairment of the cardiac function [50] than that in males. Additionally, aberrant collagen cross-linking has been reported to be more detrimental to LV diastolic and systolic performance than total collagen deposition in the ECM [4,51].…”
Section: Correlation Between LV Mir-29b Expression and Morpho-functiomentioning
confidence: 99%
“…The remodeling response also encompasses adaptive changes in the extracellular matrix (ECM), including an increased deposition of fibrillar collagens, to provide a structural scaffold and signaling control to cardiac cells, thereby preserving tissue integrity and cardiac function [4]. However, these plastic changes may become maladaptive over time, thus resulting in systolic and diastolic dysfunction, heart failure and eventually death [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…LOX encodes lysyl oxidases (LOXes) and it is the only TAAD-related gene acting at the ECM that has been clearly linked to oxidative stress so far. LOXes are a group of ECM enzymes that initiate the formation of covalent cross-linkages between collagen and elastin, generating H 2 O 2 as a by-product [ 188 ]. Experiments in Lox -deficient mice have shown that LOX-mediated cross-linking is essential for the maturation of the ECM, providing tensile strength [ 189 , 190 ].…”
Section: Redox and Oxidative Stress In Genetic Diseases Of Connectmentioning
confidence: 99%
“…The authors find that cultured human cardiac fibroblasts are targets of sST2, having a profibrotic effect that is prevented by NFkB inhibitors. The critical role played by cardiac fibroblasts in chronic heart disease is reflected in the number of studies of the volume that address their biological functions [ 5 , 7 , 9 , 10 , 11 ]. For instance, the study by Martin et al demonstrates that yet another mediator of inflammation, soluble phospholipase A2IIA (sPLA2-IIA), promotes myofibroblast differentiation and acts as a link between inflammation and fibrosis [ 9 ].…”
mentioning
confidence: 99%
“…They dissect the role of Cx43 in a model of cardiac hypertrophy induced by angiotensin II, finding that contrasting effects could be found depending on the gene dose. This study analyzed several fibrotic markers, including lysyl oxidase (LOX), a major player in the fibrotic response to a cardiac insult and prototype of a family of extracellular matrix (ECM)-modifying enzymes essential for collagen cross-linking—an issue that is reviewed by Rodriguez et al in the present volume [ 11 ].…”
mentioning
confidence: 99%